SINGLE NUCLEOTIDE POLYMORPHISM IN CATTLE AND ITS ASSOCIATION WITH SUSCEPTIBILITY TO BOVINE TUBERCULOSIS - Baladhare, Ashish; Kumar, Amit; Sharma, Deepak (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
Bovine tuberculosis is an important disease of cattle with zoonotic importance. A resource population comprising of 35 Case and 49 Control animals of indigenous cattle population was genotyped for a SNP from intergenic region of SLC6A6 gene, which have an established association with bovine tuberculosis susceptibility in Holstein-Freisian cattle population. Polymorphism in indigenous resource population at the targeted SNP revealed the presence of this SNP in indigenous cattle also. Both the alleles i.e. G and T and all possible three genotypes i.e. GG, GT and TT were observed in indigenous cattle. Low Polymorphic Information Content but high heterozygocity was observed at this SNP. The probability values showed that the genotype (P=0.38) as well as allele (P=0.53) had no significant effect on occurrence of bovine tuberculosis.
Keywords: Bovine tuberculosis; indigenous cattle; SNP; SLC6A6